Kekuasaan dan Pengetahuan: Diskursus Mitos Maskulinitas Pada Seksualitas Pemuda - Larossa Bilquis; Nurul Hidayat (Universitas Negeri Malang, 2020)
This study aims to uncover how the masculinity discourse of young immigrants in Uluwatu Bali (basecamp) exists. By using Foucault's Genaology, the insights and values they adopt one by one must be dismantled to see what logic they are constructs. This research using qualitative method with fenomenology approach, which used foucoult framework abour sex and power. It can be said, in this research found various discourses reproduced by various sources of youth knowledge regarding the myth of masculinity which is identical to the characteristics and behavior of men who are strong, aggressive, dominant, rude, and full of egoism. In practice, they myth that their various behaviors, especially regarding their sexuality, are a manifestation of their masculinity as a male. The internet or online media and the environment in which they live are one of the sources of knowledge for young people that create discourses about the myth of masculinity. The youth in the peer group also take part in formulating discourses about ideal masculinity for their group. Free sex behavior, dare to take risks, follow wild races to cause chaos are the masculinity myths they adopt as the ideal male masculinity. This study also found that the masculinity myth was more often represented in youth sexual practices as an affirmation of control over women's bodies and sexuality in order to maintain their reputation in front of their friends and others. Penelitian ini bertujuan untuk membongkar bagaimana hadirnya diskursus maskulinitas pemuda pendatang di uluwatu Bali (basecamp). Dengan menggunakan Genaologi Foucault, pemahaman dan nilai yang mereka adopsi satu per satu harus dibongkar untuk melihat logika apa yang sebenarnya mereka bangun. Sehingga dapat ditemukan berbagai wacana yang direproduksi oleh berbagai sumber pengetahuan pemuda mengenai mitos maskulinitas diamana identik dengan sifat dan perilaku laki-laki kuat, agresif, dominatif, kasar, dan penuh egoisme. Dalam praktiknya mereka memitoskan beragam perilakunya terutama menyangkut seksualitasnya merupakan manifestasi dari maskulinitasnya sebagai laki-laki yang jantan. Internet atau media online serta lingkungan tempat tinggal mereka menjadi salah satu sumber pengetahuan pemuda yang menciptakan diskursus mengenai mitos maskulinitas tersebut. Para pemuda dalam peer groupnya juga mengambil bagian dalam merumuskan wacana-wacana mengenai maskulinitas ideal bagi kelompoknya. Perilaku seks bebas, berani mengambil resiko, mengikuti balap liar hingga menyebabkan keonaran merupakan mitos-mitos maskulinitas yang mereka adopsi sebagai maskulinitas laki-laki ideal. Penelitian ini juga menemukan jika mitos maskulinitas tersebut lebih banyak direpresentasikan kedalam praktik-praktik seksual pemuda sebagai penegasan atas penguasaan tubuh dan seksualitas perempuan demi mempertahankan reputasinya di hadapan teman-temannya dan orang lain.